'Banner of an Atomic Regiment': Morris Louis, Greenberg's Modernism, and Science, c. 1962. Issue 1 (28th January 2021) - Curley, John J.
Abstract: Around 1962, 'formalism' could indicate methodological purity in the realms of both art and science. With camps in both disciplines attempting to minimize human intervention in the realm of decision‐making, 'formalism' could take on mechanical overtones, thereby linking art and science in profound ways. This essay considers the ways in which the austere abstract paintings of Morris Louis from the years surrounding 1960 bring these dual formalisms into focus. When viewed through the criticism of Clement Greenberg and the near‐unwavering faith President Kennedy's administration placed in new technocratic ways of waging war, Louis's paintings can be seen as beatified expressions of a mechanical rationality that also brought the world to the brink of nuclear apocalypse. Through deep engagement with Greenberg's criticism and media archives, the essay forges links between Greenberg's version of Louis and the dark sides of this rationality. The article concludes by locating ways to consider Louis's paintings outside of the Greenbergian straitjacket – recapturing the strangeness and chaotic nature of the painter's practice.